Bovine Neonatal Monocytes Display Phenotypic Differences Compared With Adults After Challenge With the Infectious Abortifacient Agent Neospora caninum - Sharma, Parul; Hartley, Catherine S.; Haque, Manjurul; Coffey, Tracey J.; Egan, Sharon A.; Flynn, Robin J. (Frontiers in Immunology, 2018)
The neonatal period represents a window of susceptibility for ruminants given the abundance of infectious challenges in their environment. Maternal transfer of immunity either in utero or post-birth provides protection, however this does not compensate for potential deficits in the cellular compartment. Here we present a cellular and transcriptomic study to investigate if there is an age-related difference in the monocyte response in cattle during intra-cellular protozoan infection. We utilised Neospora caninum, an obligate intracellular protozoan parasite that causes abortion and negative economic impacts in cattle worldwide, to study these responses. We found neonatal animals had a significant greater percentage of CD14+ monocytes with higher CD80 cell surface expression. Adult monocytes harboured more parasites compared to neonatal monocytes; additionally greater secretion of IL-1β was observed in neonates. Microarray analysis revealed neonates have 535 genes significantly upregulated compared to adult with 23 upregulated genes. Biological pathways involved in immune response were evaluated and both age groups showed changes in the upregulation of tyrosine phosphorylation of STAT protein and JAK-STAT cascade pathways. However, the extent to which these pathways were upregulated in neonates was much greater. Our findings suggest that neonates are more resistant to cellular invasion with protozoan parasites and that the magnitude of the responses is related to significant changes in the JAK-STAT network.